Flexible hydrogen fuel cell fabricated on paper with embedded aluminium foil - Wang Yifei; Kwok Holly; Zhang Yingguang; Pan Wending; Leung Dennis Y.C. (E3S Web of Conferences, 2019)
Direct hydrogen fuel cells are generally heavy and rigid systems based on metal or plastic materials, which are not suitable for various miniwatt and flexible devices. In this study, we have developed a lightweight and flexible fuel cell based on paper substrate embedded with an Al foil inside, which is used as an in-situ hydrogen source by reaction with an electrolyte solution during operation. Benefited from the inhibited hydroxyl transportation by the porous cellulose network, the vigorous Al corrosion reaction is well controlled even though strong alkaline electrolyte is adopted, so that the fuel cell can be discharged for more than 5 hours at 1 mA cm-2 (0.83 V) with only 3.5 mg Al foil. The corresponding faradaic and energy efficiencies are as high as 72% and 18.3%, respectively. The fuel cell flexibility is also quite good when facing different bending angles. Considering its moderate power output, this flexible paper-based hydrogen fuel cell is especially suitable for powering various miniwatt and flexible devices, such as wearable electronics, biosensors, RFID tags, etc. However, higher power can be obtained by suitable stacking of the fuel cell.